Injectable thermosensitive antibiotic-laden chitosan hydrogel for regenerative endodontics - Reis-Prado, Alexandre Henrique dos (2025)
Injectable biomaterials, such as thermosensitive chitosan (CH)-based hydrogels, present a highly translational potential in dentistry due to their minimally invasive application, adaptability to irregular defects/shapes, and ability to carry therapeutic drugs. This work explores the incorporation of azithromycin (AZI) into thermosensitive CH hydrogels for use as an intracanal medication in regenerative endodontic procedures (REPs). The morphological and chemical characteristics of the hydrogel were assessed by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and Fourier transform infrared spectroscopy (FTIR). The thermosensitivity, gelation kinetics, compressive strength, cytocompatibility, and antibacterial efficacy were evaluated according to well-established protocols. An in vivo model of periapical disease and evoked bleeding in rats' immature permanent teeth was performed to determine disinfection, tissue repair, and root formation. AZI was successfully incorporated into interconnected porous CH hydrogels, which retained their thermosensitivity. The mechanical and rheological findings indicated that adding AZI did not adversely affect the hydrogels’ strength and injectability. Incorporating 3 % and 5 % AZI into the hydrogels led to minimal cytotoxic effects compared to higher concentrations while enhancing the antibacterial response against endodontic bacteria. AZI-laden hydrogel significantly decreased E. faecalis biofilm compared to the controls. Regarding tissue response, the 3 % AZI-laden hydrogel improved mineralized tissue formation and vascularization compared to untreated teeth and those treated with double antibiotic paste. Our findings demonstrate that adding 3 % AZI into CH hydrogels ablates infection and supports neotissue formation in vivo when applied to a clinically relevant model of regenerative endodontics.